First-line Nurse Managerial Competence and Its Influencing Factors in Public Jordanian Hospitals - Iblasi, Abdulkareem S.; Makahleh, Samer; Aungsuroch, Yupin; Gunawan, Joko; Juanamasta, I Gede (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: First-line Nurse Managers (FLNMs) occupy pivotal positions within healthcare systems and are responsible for various administrative and caregiving functions. While FLNMs are integral to efficient healthcare services, their competencies and the factors influencing them still need to be explored in Jordan. In light of the need for more research on FLNM competencies in Jordan, this study is paramount for advancing healthcare in the country.Purpose: This study aimed to analyze FLNM competence and its influencing factors within the unique context of Jordan’s healthcare system.Methods: As a cross-sectional study, this research leveraged online platforms to distribute questionnaires to 130 FLNMs across three public hospitals in Jordan’s central region using a random sampling method. Univariate analysis comprised numerical data (Mean, median, mode, SD) and categorical data (percentage and proportion). Pearson, independent t-test, and multiple linear regression were used to analyze the data.Results: Based on responses from 130 FLNMs, the study’s results demonstrate their average age to be approximately 37.8 years, with a significant proportion holding master’s degrees, indicating a highly educated cohort. Notably, many FLNMs are charge nurses, reflecting their extensive experience and commitment to enhancing their leadership competencies. The study found no significant correlation between age and FLNM competencies, suggesting that competence is not solely contingent upon years of experience or age (p>0.05). The research revealed that the highest to the lowest significance in FLNM performance were leadership training (b=21.15, 95%CI=7.70-34.60, p=0.002), gender-based disparities (b=16.50, 95%CI=4.41-28.58, p=0.008) and social status (b=7.86, 95%CI=1.13-14.60, p=0.02), respectively. Conclusion: FLNMs exhibit high competence, influenced by leadership training, gender disparities, and social status. The research highlights the need for tailored training and support programs to improve the competencies of FLNMs in Jordan’s healthcare system, highlighting gender-based differences and the need for personalized healthcare management strategies to improve healthcare quality.